Relationship of neurocognition and treatment retention in subjects on opioid agonist treatment. - Ghosh, Abhishek; Rana, Devender Kumar; Basu, Debasish; Mattoo, Surendra K.; Roub, Fazle; Bammidi, Ravi (Journal of Substance Use, 2023)
Opioid dependence affects several neurocognitive domains, which can negatively affect the treatment outcome. Examining the relationship between neurocognitive functions and short-term treatment retention in subjects on buprenorphine-naloxone-based agonist treatment. We recruited 56 subjects (aged between 18 and 45 years) registered between March 2017 and December 2017. We excluded subjects dependent on other substances (except cannabis and tobacco), along with medical and other psychiatric comorbidities. During the first week of the agonist treatment, we assessed executive function, decision-making, attention, psychomotor speed, and working memory with the Wisconsin card sorting test (WCST), Iowa gambling test (IGT), and Trail making and verbal and visual N-back tests. Treatment retention was assessed after 12 weeks. The mean age of the subjects was 26 (±5.9) years. Twenty-eight (50%) subjects were retained in the treatment. Neurocognitive functions at the treatment entry did not differ between subjects retained in the treatment and those who dropped out. A higher severity and lower duration of dependence and use were associated with higher treatment discontinuation. The regression model, with the cognitive functions and significant clinical variables, could explain 38% variance for treatment retention. Neurocognitive functions at the treatment entry did not predict retention in opioid agonist treatment. There is some evidence of baseline cognitive functions predicting treatment retention in substance use disorders We wanted to test it in a group of patients on buprenorphine (naloxone)-based agonist management Relevant clinical and demographic variables were controlled for Executive functions, decision-making, attention, psychomotor speed, and working memory at the treatment entry did not predict retention at the end of three months Longer duration of opioid use (and dependence) was associated with better treatment retention